Archaeal-type lysyl-tRNA synthetase in the Lyme disease spirochete Borrelia burgdorferi - Ibba, Michael (The National Academy of Sciences of the USA, 1997)
Lysyl-tRNAs are essential for protein biosynthesis by ribosomal mRNA translation in all organisms. They are synthesized by lysyl-tRNA synthetases (EC 6.1.1.6), a group of enzymes composed of two unrelated families. In bacteria and eukarya, all known lysyl-tRNA synthetases are subclass IIc-type aminoacyl-tRNA synthetases, whereas some archaea have been shown to contain an unrelated class I-type lysyl-tRNA synthetase. Examination of the preliminary genomic sequence of the bacterial pathogen Borrelia burgdorferi, the causative agent of Lyme disease, indicated the presence of an open reading frame with over 55% similarity at the amino acid level to archaeal class I-type lysyl-tRNA synthetases. In contrast, no coding region with significant similarity to any class II-type lysyl-tRNA synthetase could be detected. Heterologous expression of this open reading frame in Escherichia coli led to the production of a protein with canonical lysyl-tRNA synthetase activity in vitro. Analysis of B. burgdorferi mRNA showed that the lysyl-tRNA synthetase-encoding gene is highly expressed, confirming that B. burgdorferi contains a functional class I-type lysyl-tRNA synthetase. The detection of an archaeal-type lysyl-tRNA synthetase in B. burgdorferi and other pathogenic spirochetes, but not to date elsewhere in bacteria or eukarya, indicates that the gene that encodes this enzyme has a common origin with its orthologue from the archaeal kingdom. This difference between the lysyl-tRNA synthetases of spirochetes and their hosts may be readily exploitable for the development of anti-spirochete therapeutics.